(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2025)
The objective of this research is to evaluate the behavioral dynamics of the shares of large pharmaceutical companies in the world in the period from 2016-2020, and the impact of the presence of COVID-19 on the finances of these companies. The analysis of the information was carried out by means of the statistical package R version 3.6.1 with interaction with the database reported by the Yahoo Finance portal through time series, where the variables evaluated were: share value at the opening and closing, financial performance, volume of shares issued. It was found that the statistics and economic indexes associated with large pharmaceutical companies in the first half of the year 2020 fell sharply in the stock market, having an effect on returns and on the volume of shares sold daily. With the development of COVID-19 vaccines, pharmaceutical companies generally increased profits, recovering from the crisis associated with the pandemic.